Comparative study on structural behaviour of circular and square section-Concrete Filled Steel Tube (CFST) and Reinforced Cement Concrete (RCC) stub column. (February 2021) - Reddy, Gosala Sai Ram; Bolla, Madhusudhan; Patton, M. Longshithung; Adak, Dibyendu
Abstract: The present research work is focused on the experimental and numerical studies on the structural behaviour of Concrete Filled Steel Tube (CFST) and Reinforced Cement Concrete (RCC) stub columns of different concrete grade. The experimental result of rectangular and square stub column of both RCC and CFST have been compared with a Finite Element (FE) study using ABAQUS platform. The concrete mix of M20, M25, M30 grade is used for the preparation of both RCC and CFST. Further in parametric study the structural dimensions of both CFST and RCC stub columns are kept same. The study has been carried out for both CFST and RCC stub columns by varying Depth/thickness ( D / t ) ratios in CFST stub columns (19.2, 23.5, 30.67, 45 for square sections and 23.20, 28.50, 37.33, 55.00 for circular sections), Steel percentage in RCC stub columns (8.69%, 12.62%, 16.30%, 19.75% for square sections and 7.20%, 10.50%, 13.50%, 16.40% for circular sections) and Concrete cube strengths (20, 25 and 30 MPa) for both CFST and RCC stub columns). The main aim of the study was to make a comparison on the structural behaviour of CFST and RCC stub columns. The comparison results show that the axial capacity of the CFST stub columns on an average is 50% and 55% more than the RCC stub columns with square section and circular sections respectively. Also, the effect of thickness of steel tubes, concrete cube strength and steel percentage is also studied.